VFP: A Virtual Switch Platform for Host SDN in the Public Cloud - Firestone, Daniel (USENIX Symposium on Networked Systems Design and Implementation (NSDI) 2017, 2017)
Many modern scalable cloud networking architectures rely on host networking for implementing VM network policy - e.g. tunneling for virtual networks, NAT for load balancing, stateful ACLs, QoS, and more. We present the Virtual Filtering Platform (VFP) - a programmable virtual switch that powers Microsoft Azure, a large public cloud, and provides this policy. We define several major goals for a programmable virtual switch based on our operational experiences, including support for multiple independent network controllers, policy based on connections rather than only on packets, efficient caching and classification algorithms for performance, and efficient offload of flow policy to programmable NICs, and demonstrate how VFP achieves these goals. VFP has been deployed on >1M hosts running IaaS and PaaS workloads for over 4 years. We present the design of VFP and its API, its flow language and compiler used for flow processing, performance results, and experiences deploying and using VFP in Azure over several years.